2018
DOI: 10.1002/gj.3385
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of an elusive mid‐14th century earthquake in the central Himalaya: Consilience of evidence from Nepal and India

Abstract: The timing and size of the last great earthquake in the central Himalaya continues to excite scientific controversy, despite a decade of palaeoseismological investigations. The studies along the frontal thrust in the Indian part of the central Himalaya disclose a faulting event between 14th and 15th century, and a dominant view presupposes the 1505 CE earthquake as the likely source. Here we evaluate the database along with independent inputs to determine the timing of the last faulting event on the frontal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…The last offset has been attributed to the historical Uttarkashi earthquake of 1803 and the penultimate faulting, with lesser confidence, is ascribed to the 1505 earthquake. Paleoseismic investigations in an adjacent new trench section on a shared scarp by Rajendran et al (2018b)did not find any supporting evidence for the previous interpretation of the trench stratigraphy by Malik et al (2016) that suggested multiple displacements cutting across a varied set of deformed stratigraphic units leading up to the 1803 rupture. The latter interpretation posits a single episode of a low-angle displacement at this site possibly occurred between 1266 and 1636 CE and disavows the claim that the 1803 earthquake ruptured the MFT.…”
Section: Garhwal and Kumaun Himalayamentioning
confidence: 61%
See 1 more Smart Citation
“…The last offset has been attributed to the historical Uttarkashi earthquake of 1803 and the penultimate faulting, with lesser confidence, is ascribed to the 1505 earthquake. Paleoseismic investigations in an adjacent new trench section on a shared scarp by Rajendran et al (2018b)did not find any supporting evidence for the previous interpretation of the trench stratigraphy by Malik et al (2016) that suggested multiple displacements cutting across a varied set of deformed stratigraphic units leading up to the 1803 rupture. The latter interpretation posits a single episode of a low-angle displacement at this site possibly occurred between 1266 and 1636 CE and disavows the claim that the 1803 earthquake ruptured the MFT.…”
Section: Garhwal and Kumaun Himalayamentioning
confidence: 61%
“…Lately, Rajendran et al (2018b) evaluated the database along with independent inputs to determine the timing of the last faulting event on the frontal thrust of the central Himalaya. The newly geological data from multiple trenches across the frontal thrust (including the farwestern Nepal) show that the last faulting event occurred between 13 th and 14 th centuries -the time interval coinciding with the 1344 CE earthquake (Fig.…”
Section: Garhwal and Kumaun Himalayamentioning
confidence: 99%
“…Rajendran et al (2018b) concluded that the rupture of 1803 earthquake in the Kumaun Garhwal Himalaya did not extend up to the MFT. Rajendran et al (2018c) also provided estimates of the extent of rupture from the available publications (Fig. 14).…”
Section: Seismotectonic Studiesmentioning
confidence: 99%
“…They propose that the volcanic pumice from Andaman is geochemically and tectonically analogous to those from the Mariana arc and Okinawa Trough of the Pacific Ocean. Rajendran et al (—this issue) assemble evidence from Nepal and India to gain insights on the elusive mid‐14th century earthquake in the central Himalaya. Based on multiple pieces of evidence, in combination with new data inputs from two trench locales, suggest the 1344 CE as the last of the medieval sequence of earthquakes.…”
mentioning
confidence: 99%
“…Rajendran et al (2019-this issue) assemble evidence from Nepal and India to gain insights on the elusive mid-14th century earthquake in the central Himalaya. Based on multiple pieces of evidence, in combination with new data inputs from two trench locales, suggest the 1344 CE as the last of the medieval sequence of earthquakes.…”
mentioning
confidence: 99%